2011
DOI: 10.1371/journal.pone.0021764
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-Exposed Biofilm Microbial Communities Are Naturally Resistant to Chernobyl Ionizing-Radiation Levels

Abstract: BackgroundThe Chernobyl accident represents a long-term experiment on the effects of exposure to ionizing radiation at the ecosystem level. Though studies of these effects on plants and animals are abundant, the study of how Chernobyl radiation levels affect prokaryotic and eukaryotic microbial communities is practically non-existent, except for a few reports on human pathogens or soil microorganisms. Environments enduring extreme desiccation and UV radiation, such as sunlight exposed biofilms could in princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 86 publications
(100 reference statements)
3
48
0
1
Order By: Relevance
“…A growing number of reports also associate sensitivity to Alternaria with asthma (5,(7)(8)(9), possibly due to the high spore germination rate of members of this genus and their release of protease (10). The rise in the incidence of asthma among adults and children may be linked to global climate changes and reductions in the ozone layer and the accompanying increased solar radiation (5,11,12). Since the melanin of fungal cell walls provides protection against UV, ionizing, and gamma radiation (13), this pigment may contribute to the higher survival rates and competitive abilities of melanized fungi, leading to further environmental proliferation.…”
mentioning
confidence: 99%
“…A growing number of reports also associate sensitivity to Alternaria with asthma (5,(7)(8)(9), possibly due to the high spore germination rate of members of this genus and their release of protease (10). The rise in the incidence of asthma among adults and children may be linked to global climate changes and reductions in the ozone layer and the accompanying increased solar radiation (5,11,12). Since the melanin of fungal cell walls provides protection against UV, ionizing, and gamma radiation (13), this pigment may contribute to the higher survival rates and competitive abilities of melanized fungi, leading to further environmental proliferation.…”
mentioning
confidence: 99%
“…Indeed, barn swallows Hirundo rustica have germline mutation rates for neutral microsatellite markers increased by a factor 2-10 ( Ellegren et al 1997). Numerous other studies have shown increases in mutation rates from bacteria (Ragon et al 2011) to humans (Dubrova et al 1996), with contaminated areas around Chernobyl having mutation rates that are increased 2-20-fold relative to controls . The effects of exposure to ionizing radiation may be long lasting due to genomic instability, causing DNA to be particularly susceptible to future environmental perturbations even after one or more generations (Morgan et al 1996).…”
Section: Identification Of Environmental Indicators Of Ionizing Radiamentioning
confidence: 92%
“…Most bacteria may have a higher resistance to radiation than mammalian cells but controlled in-vitro studies fail to assess how competition between bacteria can be affected by radiation. From a microbial studies standpoint, it seems that only low and high levels of radiation are indicative of competition while all ranges between will allow one species to overgrow the others (Ragon et al, 2011).…”
Section: Bacterial Radioprotection and Hormesismentioning
confidence: 99%
“…For example, a study performed in Chernobyl showed that bacterial competition is drastically affected by ionizing radiation (Ragon et al, 2011). In terms of the mammalian microbiota, this would not be a beneficial situation.…”
Section: Bacterial Radioprotection and Hormesismentioning
confidence: 99%